Conformation and component parts of the carcass of Philippine native goat - Tambunan, Reny Debora; Roxas, N.P; Pamungkas, D (Indonesian Journal of Animal and Veterinary Sciences, 2005)
Only limited work has been done to assess the potential of Philippines native goat in terms of conformation and component parts of the carcass. Thus, an experiment has been conducted at Institute of Animal Science, University of the Philippines  os Baños, Philippines to determine carcass and lean-fat-bone yield of different cuts of chevon from Philippine native goat.  Result showed that among the wholesale cuts of chevon, shoulder had significantly higher separable lean content (8.80% of LW) than leg, loin, rib, and neck. Based on % wholesale cuts (WC), however, the leg had significantly higher value (69.18%) than the other chevon cuts. Loin had significantly higher separable fat (1.67% of LW) than the other chevon cuts. Shoulder had significantly higher separable bone (4.62% of LW). Based on %WC, however, rib had significantly higher separable bone (53.36%) than the other cuts. The shoulder had significantly higher boneless recovery (9.39% of LW) than other chevon cuts.     Key Words: Chevon, Carcass, Live Weight, Wholesale Cut